Factors Influencing Teacher Job Satisfaction in Islamic Boarding Schools: Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Guru di Lingkungan Pondok Pesantren - Silvia Putri Novitasari; Sukarman Sukarman; Hasanah Fitriya (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
Teacher job satisfaction is a critical factor that influences the quality of learning in educational institutions. This study aims to identify and analyze the determinants of teacher job satisfaction at the Ath-Thahiriyah Islamic Boarding School in Jepara. Employing a qualitative case study approach, the research was conducted on April 30, 2025, involving 12 active teachers selected through purposive sampling. Data were collected through in-depth interviews, participatory observations, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing/verification. The findings reveal that teacher job satisfaction is shaped by several key factors: a supportive work environment, adequate learning facilities, interpersonal relationships, appropriate task assignment, teaching experience, and responsive management support. In addition, the integration of Islamic spiritual values such as sincerity, responsibility, and service as an act of worship emerges as a distinctive dimension that differentiates this context from previous studies in general schools. The implications highlight the need for pesantren management to strengthen professional development, reward systems, and spiritual reinforcement in order to create a sustainable and positive working climate.